PENGARUH MOTIVASI, SELF EFFICACY, KEMAMPUAN, PERTIMBANGAN PASAR KERJA, DAN PENGHARGAAN FINANSIAL TERHADAP MINAT MAHASISWA AKUTANSI BERKARIR DI BIDANG PERPAJAKAN (STUDI EMPIRIS UNIVERSITAS DI KOTA PEKANBARU) - Elisa Nur; Agusti Restu; Azhari Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of motivation, self efficacy,competence, consideration of the job market, and financial awards against thecareer interest of accounting students in the field of taxation. The population inthis study was 5.818 active students majoring in Accounting Degree from theUniversity in Pekanbaru City. In this study, the sample used was 374 respondentsselected by using purposive sampling techniques. This study uses primary data bydistributing questionnaires. The analytical method used in this study is multiplelinier regression analysis. The analytical tool used in this study is StastisticalProduct and Service Solution (SPSS) version 25.0. The results of this study foundthat motivation, self efficacy, competence, consideration of the job market, andfinancial awards significantly influence α < 0.05 against career interest ofaccounting students in the field of taxation. Based on total Adjusted R Squareresult, showed that 66% variables of workin career interest can be explained byvariable of motivation, self efficacy, competence, consideration of the job market,and financial awards. And the rest of 34% can be explained by other variableswhich not included in this research.Keywords : Motivation, Self Efficacy, Competence, Consideration Of The JobMarket, Financial Awards, And Interest in Accounting Careers inThe Field Of Taxation